On not being able to sleep : psychoanalysis and the modern world - Rose, Jacqueline (Princeton University Press, 2003)
In these powerful essays, Jacqueline Rose delves into the questions that keep us awake at night, into issues of privacy and writing, exposure and shame. Do women writers--Christina Rossetti, Anne Sexton, Sylvia Plath--have a special talent for self-revelation? Or are they simply more vulnerable to the invasions of biography? What ethical questions are raised by Ted Hughes's role in Plath's writing life? What do Adrienne Rich and Natalie Angier reveal about the destiny of feminism? In its affinity with modernist writing, what can psychoanalysis tell us about the limits of knowledge--both about the most intimate components of experience and the most hallucinatory reaches of the mind? Have psychoanalytic writers today and the very institution of psychoanalysis remained faithful to the most potent and disturbing aspects of Freud's vision? Finally Rose addresses some of the most dramatic public performances of our times--the cult of celebrity with its contrasting obsessions with Princess Diana and the child murderer Mary Bell and South Africa's Truth and Reconciliation Commission which, in a stirring last essay, allows Rose to explore the ethical and political responsibilities of thought and speech in times of historical crisis.